The effects of population size on genetic parameters and mating system of sandalwood in Gunung Sewu, Indonesia - Yeni Widyana Nurchahyani; Sapto Indrioko; Eny Faridah; Atus Syahbudin (Universitas Gadjah Mada, 2015)
We combined feld observations with isoenzyme analysis to compare population demographic and its effects on genetic diversity and mating systems, among six populations of sandalwood in Gunung Sewu, Indonesia, during March to August 2015. This endangered economic-important species was originated from the southeastern parts of Indonesia, but is recently occured as new landraces in Gunung Sewu, Java island. The observed heterozygosity varied from Ho 0.184 to 0.385 in parents, and from Ho 0.083 to 0.348 in offspring levels, based on the degree of clonality and genetic base. Most of genetic variation is distributed within populations, and only 2.7% were presented among populations, that was indicated by the low DST and FST value (HT 0.30; HS 0.276; DST 2.4%; FST 7.98%). A dendrogram indicated a grouping of populations into three clusters. However, there were seemed to be no association between geographical and genetic distance. Genetic depletion occured due to (i) clonality events as result of heavy-exploitation and/or natural disturbance which induced root suckering, (ii) genetic drifts and bottleneck effects, (iii) the founder effects due to parental low diversity, and (iv) the alteration on mating systems to be more inbreeders. Some of the results confrmed a “reproductive assurance prediction” while some others were contradicting this. It seemed that genetic diversity and mating systems are not much affected by population size, but more by the parental heterozygosity and the degree of clonality. Our results emphasized the importance of populations’ genetic base or parental genetic diversity to naturally maintain the genetic and evolutionary processes under equilibrium conditions.